AB0152 Microarrays gene expression profiling of monocytes from systemic lupus erythematosus patients: novel genes and pathways involved in the disease. (12th June 2018) - Perez-Sanchez, C.; Cecchi, I.; Aguirre, M.A.; Pérez-Sánchez, L.; Luque-Tevar, M.; Barbarroja, N.; Ruiz-Limón, P.; Jiménez-Gómez, Y.; Arias de la Rosa, I.; Abalos-Aguilera, M.D.C.; Segui, P.; Collantes, E.; et al.
Abstract : Objectives: 1. To identify altered genes and pathways in monocytes from Systemic Lupus Erythematosus (SLE) patients involved in the pathogenesis of the disease. 2. To evaluate the contribution of anti-dsDNA antibodies to the regulation of these processes. Methods: Eigthy three subjects, including 53 SLE patients and 30 healthy donors (HDs), were recruited. Total RNA was extracted from monocytes isolated of 6 subjects .analyzed as exploratory cohort- and microarray studies were performed in an Agilent G4112F platform (Whole Human Genome Microarray 44k). By using the Ingenuity Pathway Analysis Software (IPA) the altered gene, pathways, and network profiles were identified and functionally categorised. The top differentially expressed genes were validated by RT-PCR in monocytes purified from all the subjects enrolled. The inflammatory profile was evaluated in serum by multiplex assay. The activation of intracellular proteins was analysed by PathScan intracellular signalling protein array. Correlation and association studies were performed with clinical and analytical variables. The effect of anti-ds-DNA antibodies in the altered gene expression signature was evaluated by in vitro studies on monocytes from HD Results: Microarray gene expression profiling identified 553 significantly altered genes in monocytes from SLE patients in relation to HDs (p<0, 05 and fold change >2). IPA analysis showed that the altered genes were mainly related to inflammatory and immunological disease (32, 4%), as well as cardiovascular (22, 5%), neurological (21, 9%), musculoskeletal (10%), renal (6, 5%), dermatological (4, 5%) and reproductive system disorders (2, 2%). The top altered canonical pathway identified was the interferon signalling, and the main altered genes, validated by RT-PCR, were PGC1-α (master regulator of mitochondrial biogenesis and oxidative stress), IFI27, IFI44, IFI44L, IFIT1, IFI6 and RSAD2 (interferon signalling), EDNRB (endothelin receptor involved in the vascular system homeostasis), SERPINB10 (serpine related to haematopoiesis and apoptosis), CDKN1B and CCDN2 (proliferation regulators), and IL22RA1 and CMKLR1 (inflammatory mediators). The altered gene signature was associated with the presence of anti-dsDNA antibodies, and clinical features of SLE (early atherosclerosis and nephropathy), and correlated with the disease activity and the levels of inflammatory serum markers (CRP, ESR, C3, C4, IL8, MCP1, IFNγ, IP10, PDGFBB). The activation of numerous intracellular signalling proteins was also noticed. In vitro studies demonstrated the modulation of several genes by effect of anti-dsDNA. Conclusions: Gene expression profile allowed the identification of relevant genes and pathways altered in monocytes of SLE patients, which were associated with the pathogenesis of the disease and modulated, at least partially, by anti-dsDNA. The identification of relevant genes whose products regulate specific pathological processes might contribute to the development of targeted therapies in SLE Acknowledgements: Funded by JA(CTS-7940) and Ministry of Health (PI15/01333 and RIER RD16/0012/0015) cofinanced with FEDER funds Disclosure of Interest: None declared